Optimizing the role of informal learning in the perspective of Islamic education during the Covid-19 pandemic - Annisa Arsya Wardani; Toto Suharto (UIN Raden Mas Said Surakarta, 2021)
Online learning is chosen during the Covid-19 pandemic. The problem that occurs is teachers as educators cannot directly supervise the development of students, so they need help from the informal educational institution.. In this context, parents take the role of facilitators during online learning. Not only limited to the educational function of parents, but it also has many roles that can be optimized so that children can grow and develop properly. The purpose of this study is toportray the role of families, especially parents in optimizing their role when online learning is present during the Covid 19 pandemic. The method used in this research was qualitative descriptive. This study used the data triangulation method as a technique to measurethe validity of the data. The analysis technique used in this research was interactive model analysis. The interactive analysis included data reduction, data presentation, and conclusions. The main results of this study were parents, apart from being an educational institution, whoalso took a role of being shaping children's character and personality that is to stimulate children's linguistic intelligence. Parents can also stimulate children's intrapersonal intelligence by adapting to behavior that is appropriate to the local cultural environment. The contribution of this research includes the function of parents which is not only maximizing scientific education but also deepening the internalization of spiritual and religious values in children, as well as building good communication is needed to optimize the role of parents to children.